PERSEPSI MAHASISWA AKUNTANSI MENGENAI FAKTOR-FAKTOR YANG MEMBEDAKAN PEMILIHAN KARIR - Mariana, Vina; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine the perception of accounting students about some factors which have influence to the selection of career. The Perception of the students is measured by using salary, professional training, professional recognition, social values, work environment, labor market and personality consideration.This research is quantitative research. The data collection is carried out by issuing questionnaires to the accounting undergraduate students of STIESIA in Surabaya class of 2011 and 2012. The sample collection technique has been done by using purposive sampling. So, 91 respondents have been selected as samples. The data analysis has been performed by using multivariate analysis which is done by using one way anova and the SPSS 20 version.Based on the result of hypothesis test it can be concluded that there is difference of perception of students about the selection of career when it is reviewed from salary factor, professional training, professional recognition, social values, work environment, and labor market consideration. Meanwhile, when it is reviewed from personality factor there is no difference of perception of students.Keyword : career selection, accounting, and work environment